2013
DOI: 10.5194/bg-10-4383-2013
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of vertical chlorophyll <i>a</i> in the Arctic Ocean: impact of the subsurface chlorophyll maximum on regional, seasonal, and annual primary production estimates

Abstract: Abstract. Predicting water-column phytoplankton biomass from near-surface measurements is a common approach in biological oceanography, particularly since the advent of satellite remote sensing of ocean color (OC). In the Arctic Ocean, deep subsurface chlorophyll maxima (SCMs) that significantly contribute to primary production (PP) are often observed. These are neither detected by ocean color sensors nor accounted for in the primary production models applied to the Arctic Ocean. Here, we assemble a large data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
126
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 98 publications
10
126
1
Order By: Relevance
“…Thereby, we suggest that the surface F L can also be reasonably used to predict the upper layer phytoplankton size structure. This might be due to the shallow bathymetry and SCM depth (∼ 20 m) associated with the nitracline depth (Brown et al, 2015) compared to the higher Arctic Ocean where a deeper SCM (> 40 m) is commonly found (Ardyna et al, 2013). Furthermore, the significantly shallower depth of the PP maximum compared to the depth of the SCM (Fig.…”
Section: Evaluation Of Performance Of Satellite Algorithmsmentioning
confidence: 96%
See 2 more Smart Citations
“…Thereby, we suggest that the surface F L can also be reasonably used to predict the upper layer phytoplankton size structure. This might be due to the shallow bathymetry and SCM depth (∼ 20 m) associated with the nitracline depth (Brown et al, 2015) compared to the higher Arctic Ocean where a deeper SCM (> 40 m) is commonly found (Ardyna et al, 2013). Furthermore, the significantly shallower depth of the PP maximum compared to the depth of the SCM (Fig.…”
Section: Evaluation Of Performance Of Satellite Algorithmsmentioning
confidence: 96%
“…Hill et al 2005, Ardyna et al, 2013. The omission of the SCM sometimes causes a large error in the satellite estimation of PP eu in the high Arctic (Hill et al, 2013).…”
Section: Evaluation Of Performance Of Satellite Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the similarity could be due to biased seasonal coverage by field studies in ice-free waters, introducing more measurements collected in late summer and fall (i.e., September), thus lowering the ice-free iNPP average (not shown). Alternatively, the similarity in simulated iNPP values in ice-free and ice-influenced areas could result from the averaging of regional differences previously observed in field and satellite-derived NPP data [e.g., Arrigo et al, 2012;Hill et al, 2013;Ardyna et al, 2013] as well as in model simulations [e.g., Zhang et al, 2015]. Recently, Jin et al [2016] showed that simulated under-ice production is also regionally different (i.e., higher in the Arctic shelves, possibly due to enhanced nutrient supply) [Zhang et al, 2015], but not necessarily related to the recent decrease in sea ice concentration, especially in marginal ice zones.…”
Section: /2016jc011993mentioning
confidence: 99%
“…It seems likely that the greater thickness of Arctic sea ice and its impermeability for almost all of the period (Zhou et al, 2013) inhibits the upwelling of iodine through capillary channels in the ice (Saiz-Lopez and Boxe, 2008), and so atmospheric iodine in the Arctic is instead associated with air flow above ocean surfaces. Considering that the main atmospheric iodine source is biological primary production in colder waters, the iodide concentration is lower (R. Chance, University of York, personal communication, 2013) and so the production of HOI and I 2 from the uptake of O 3 at the ocean surface is less significant, the primary biological bloom occurs around Svalbard during the March-May period (Ardyna et al, 2013), and that iodine is primarily emitted from the open-ocean surface, we can now evaluate the change in sea ice extension around Svalbard during the period covered by the firn core. The iodine profiles from Svalbard show two periods with high concentrations: between 2004-2006 and 2011-2012 where concentrations exceeded 50 pg g −1 (Fig.…”
Section: Iodine and March-may Sea Icementioning
confidence: 99%